A road base construction method using multi-element waste residue compound to replace water-stable gravel aggregate

CN122918907APending Publication Date: 2026-10-16JIANGSU WUXI TRANSPORTATION HIGHER VOCATIONAL & TECH SCHOOL
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611182392.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-05
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

[0003]天然砂石骨料属于不可再生资源,长期大规模开山采石已对生态环境造成严重破坏,优质碎石资源日趋枯竭,采购成本不断攀升,且远距离运输进一步增加了能耗与碳排放,与国家“双碳”战略目标及绿色公路建设要求不相适应

Benefits of technology

(1)本发明采用分级钢渣完全替代天然碎石作为粗骨料,以石粉替代天然砂作为细骨料,骨料固废利用率高,有效减少天然石材开采,保护生态环境;同时大量消纳钢渣、电石渣、脱硫石膏、石粉等工业固体废弃物,减少土地占用及环境污染,绿色低碳效益显著。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

This invention relates to the field of road base construction technology, and more particularly to a method for constructing road bases using a multi-component waste residue compound as a substitute for water-stabilized crushed stone aggregate. The mixture used in this construction method for road base construction consists of aggregates, composite cementitious materials, and water. The aggregates include coarse aggregates and fine aggregates, with the coarse aggregates accounting for 65%–75% of the total aggregate mass. The composite cementitious material is added at 3.5%–4.5% of the total aggregate mass. After wet mixing with water, the moisture content of the mixture is 3.8%–6%, and the dry density is ≤2.58 g / cm³. 3 This invention uses graded steel slag to completely replace natural crushed stone as coarse aggregate and stone powder to replace natural sand as fine aggregate. It has a high utilization rate of aggregate solid waste, effectively reduces the mining of natural stone, and protects the ecological environment. At the same time, it disposes of a large amount of industrial solid waste such as steel slag, carbide slag, desulfurization gypsum, and stone powder, reducing land occupation and environmental pollution, and has significant green and low-carbon benefits.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of road engineering base course construction technology, and in particular to a road base course construction method that uses a multi-component waste residue compound to replace water-stabilized crushed stone aggregate. Background Technology

[0002] In traditional road base construction, cement-stabilized (or "water-stabilized") crushed stone materials are the most widely used, with natural crushed stone as aggregate and ordinary Portland cement as the main cementing system. However, with the continuous advancement of infrastructure construction in my country, this technical approach faces increasingly prominent contradictions in terms of resource and environmental carrying capacity, industrial solid waste disposal, and long-term engineering performance.

[0003] Natural sand and gravel aggregates are non-renewable resources. Long-term, large-scale quarrying has severely damaged the ecological environment, leading to a depletion of high-quality crushed stone resources, continuously rising procurement costs, and increased energy consumption and carbon emissions due to long-distance transportation. This is incompatible with the national "dual-carbon" strategic goals and the requirements for green highway construction. Industries such as steel, chemicals, power, and stone processing generate large amounts of industrial solid waste annually, including steel slag, carbide slag, desulfurization gypsum, and stone powder. Currently, the comprehensive utilization rate is generally low, with most waste disposed of through open-air storage. This not only occupies significant land resources but also poses environmental risks such as dust pollution and soil and groundwater acidification / alkalization due to long-term storage. The resource utilization of solid waste is urgently needed. In existing cement-stabilized crushed stone base course technologies, pure cement, as the sole cementing component, undergoes a violent hydration reaction and has a high heat of hydration. Under temperature changes and drying conditions, it is prone to significant drying shrinkage and thermal shrinkage deformation, leading to through-cracks in the base course structure. Once cracks form, surface water seeps down along them, and under repeated traffic loads, it can easily cause secondary problems such as base layer delamination, settlement, and pumping, severely weakening the integrity and durability of the pavement structure, significantly increasing later maintenance costs, and shortening the road's service life. Furthermore, to meet strength requirements, the cement content is often too high, further increasing material costs and resulting in poor economic efficiency.

[0004] In response to the above-mentioned shortcomings, there is an urgent need to develop an alternative construction technology that can efficiently dispose of diverse industrial waste residues, improve the crack resistance of the base layer, and reduce project costs. Summary of the Invention

[0005] To address the shortcomings of existing technologies, the present invention aims to provide a method for constructing road base courses using a composite of multiple waste residues as a substitute for water-stabilized crushed stone aggregate.

[0006] To achieve the above objectives, the present invention adopts the following technical solution: A method for constructing a road base course using a multi-component waste residue compound as a substitute for water-stabilized crushed stone aggregate is characterized in that the mixture used for road base course construction consists of aggregate, composite cementitious material, and water. The aggregate includes coarse aggregate and fine aggregate, with the coarse aggregate accounting for 65%–75% of the total aggregate mass. The composite cementitious material is added at 3.5%–4.5% of the total aggregate mass. The moisture content of the mixture after wet mixing with water is 3.8%–6%, and the dry density is ≤2.58 g / cm³. 3 The construction method includes the following steps: S1. Weigh out the coarse aggregate, fine aggregate, and composite cementitious material according to the proportion of the mixture. S2. Dry mix the coarse aggregate and fine aggregate evenly, then add the composite cementitious material and dry mix evenly. Add water according to the moisture content of the mixture and wet mix. After mixing evenly, discharge the material. S3. The paving is carried out by sealed tank trucks to the construction site and continuously paved by a paver. The paving speed is controlled at 2 to 3 m / min, and the loose paving thickness is controlled according to the compaction coefficient of 1.25 to 1.30. S4. Compact the molding process, achieving a compaction degree ≥98%; S5. After compaction, cover with geotextile and water for curing for no less than 7 days. During the curing period, traffic shall be closed.

[0007] Specifically, the aggregates in this invention are all industrial waste residue, with no natural crushed stone added; the composite cementitious material replaces traditional pure cement, resulting in a mild hydration reaction and minimal shrinkage deformation, effectively inhibiting the formation of dry shrinkage and thermal shrinkage cracks in the base layer. The above mix proportions and core control parameters were optimized through experiments, and the mixture achieves optimal density and strength within this parameter range. The mixing time is appropriately extended during mixing to ensure a uniform mixture without segregation or agglomeration; the discharge temperature is controlled to prevent premature hydration of the cementitious material, which could affect later strength. Potholes, segregation, and road surface undulation defects are addressed promptly during paving. The entire road section is closed to traffic during the curing period, prohibiting any vehicle passage, and the base layer surface is kept moist throughout the process.

[0008] Based on the above technical solutions, preferably, the coarse aggregate is graded steel slag, which is composed of three particle size specifications: 19-26.5mm, 9.5-19mm and 4.75-9.5mm, with a mass ratio of 1:1.4-1.6:1.35-1.41.

[0009] Specifically, by using steel slag coarse aggregate of the above three particle size specifications in combination with fine aggregate, a dense skeleton structure can be formed with continuous gradation and excellent interlocking effect, ensuring the overall strength and stability of the base layer.

[0010] Based on the above technical solutions, preferably, the fine aggregate is stone powder, which is composed of two specifications: a particle size of 2.35-4.75 mm and a particle size of 0-2.35 mm, with a mass ratio of 1:4.5-5.5.

[0011] Specifically, the stone powder fine aggregate and steel slag coarse aggregate are reasonably mixed to form a continuous gradation. The fine aggregate fully fills the voids in the coarse aggregate skeleton, improving the density of the mixture. When the stone powder fine aggregate arrives at the site, the mud content is controlled to be ≤3%, and the moisture content fluctuation is controlled within ±0.5%.

[0012] Based on the above technical solutions, preferably, the composite cementitious material is composed of mineral powder, carbide slag, and desulfurized gypsum, with a mass ratio of 25-26:6-7:1.

[0013] Specifically, mineral powder is the main cementing component, carbide slag acts as an alkaline activator to activate the activity of mineral powder, and desulfurized gypsum plays a role in regulating setting and strengthening. The three work together to form a ternary composite cementing system, which replaces traditional pure cement, significantly reduces the heat of hydration, and significantly improves crack resistance.

[0014] Based on the above technical solutions, preferably, in step S1, the coarse aggregate undergoes aging and stabilization treatment to dissolve free calcium oxide.

[0015] Specifically, the aging and stabilization treatment of steel slag fully dissolves free calcium oxide, preventing damage to the pavement structure caused by the hydration and expansion of free calcium oxide in the later stages of the base course.

[0016] Based on the above technical solutions, preferably, in step S2, the discharge temperature is ≤60℃.

[0017] Specifically, controlling the discharge temperature below 60℃ can effectively prevent premature hydration of composite cementitious materials, ensuring the workability and later strength development of the mixture.

[0018] Based on the above technical solutions, preferably, in step S3, the transportation time of the sealed tanker truck is ≤1 hour.

[0019] Specifically, using sealed tank trucks for transportation can prevent moisture evaporation and aggregate segregation in the mixture, and the transportation time can be controlled within 1 hour to ensure that the mixture is laid and compacted at the optimal moisture content.

[0020] Based on the above technical solutions, preferably, in step S4, the compaction molding process specifically includes: Initial compaction: Static compaction with a steel wheel roller 1-2 times, travel speed 2-3 km / h; Compaction: Vibratory roller high-frequency low-amplitude compaction 3-4 times, travel speed 3-4 km / h; Final compaction: Apply static compaction with a rubber-tired roller 1-2 times at a speed of 2-3 km / h to eliminate wheel tracks and ensure a smooth and dense base surface.

[0021] Specifically, the initial compaction uses a steel wheel roller to statically compact the mixture to initially stabilize it; the secondary compaction uses a vibratory roller to roll it at high frequency and low amplitude, which is a key process to achieve a compaction degree of over 98%; and the final compaction uses a rubber-tired roller to statically compact and knead the mixture to eliminate wheel tracks and seal the surface.

[0022] Based on the above technical solutions, preferably, the 7-day unconfined compressive strength of the formed road base layer is not less than 4.1 MPa.

[0023] Specifically, the road base formed according to the above mix proportions and construction methods has a dense structure, strong overall stability, and a stable 7-day unconfined compressive strength of 4.1 MPa. Its bearing capacity and durability meet the requirements for road bases at all levels.

[0024] Based on the above technical solutions, the preferred method is applicable to the base construction of municipal roads, highways, industrial park roads, factory roads, and rural roads.

[0025] Specifically, the construction process of this invention is fully compatible with existing cement-stabilized crushed stone construction equipment, requiring no additional specialized equipment, and is suitable for large-scale construction of various road projects; it can dispose of large quantities of industrial solid waste such as steel slag, carbide slag, desulfurized gypsum, and stone powder, resulting in high solid waste utilization and lower overall project cost compared to traditional water-stabilized crushed stone base courses.

[0026] Compared with the prior art, the present invention has the following beneficial effects: (1) This invention uses graded steel slag to completely replace natural crushed stone as coarse aggregate and stone powder to replace natural sand as fine aggregate. The utilization rate of aggregate solid waste is high, which effectively reduces the mining of natural stone and protects the ecological environment. At the same time, it disposes of a large amount of industrial solid waste such as steel slag, carbide slag, desulfurized gypsum, and stone powder, reducing land occupation and environmental pollution, and has significant green and low-carbon benefits.

[0027] (2) The present invention uses a ternary composite cementitious system of mineral powder-carbide slag-desulfurized gypsum to replace traditional pure cement. The hydration reaction is mild, the heat of hydration is low, and the shrinkage deformation is small, which can effectively inhibit the generation of dry shrinkage cracks and thermal shrinkage cracks in the base layer. By optimizing the aggregate gradation to form a dense skeleton structure, the 7-day unconfined compressive strength of the finished road base layer is not less than 4.1 MPa. The overall strength, density and durability are excellent, which can meet the requirements of road base layers at all levels.

[0028] (3) The industrial waste raw materials used in this invention are inexpensive and can replace expensive natural crushed stone and cement. The overall engineering cost is lower than that of traditional water-stabilized crushed stone base courses, and the cost of solid waste disposal can also be reduced. The construction process is fully compatible with existing cement-stabilized crushed stone construction equipment, and no new special equipment is required. The standardization is high and it can be widely used in various road base courses such as municipal roads, highways, park roads, factory roads and township roads. It has high promotion value. Detailed Implementation

[0029] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, and not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.

[0030] It should be noted that, in the embodiments of the present invention, the dry density is determined according to the compaction test method specified in JTG 3441-2024 "Test Procedure for Inorganic Binder Stabilized Materials in Highway Engineering"; the 7-day unconfined compressive strength is determined according to the unconfined compressive strength test method specified in JTG 3441-2024 "Test Procedure for Inorganic Binder Stabilized Materials in Highway Engineering".

[0031] Example 1 This embodiment selects a municipal road base construction project for on-site construction. The base design thickness is 20cm. The mix proportion of the road base construction mixture is as follows: coarse aggregate is graded steel slag, accounting for 70% of the total aggregate mass; fine aggregate is stone powder, accounting for 30% of the total aggregate mass. Among them, 19-26.5mm steel slag accounts for 18% of the total aggregate mass, 9.5-19mm steel slag accounts for 27% of the total aggregate mass, and 4.75-9.5mm steel slag accounts for 25% of the total aggregate mass; 2.35-4.75mm stone powder accounts for 5% of the total aggregate mass, and 0-2.35mm stone powder accounts for 25% of the total aggregate mass. Composite cementitious material is added externally at a dosage of 4% of the total aggregate mass, with the mass ratio of mineral powder, carbide slag, and desulfurized gypsum being 77:20:3. The moisture content of the mixture is controlled at 4.69%, and the measured maximum dry density is 2.58g / cm³. 3 .

[0032] The specific implementation process is as follows: S1. Steel slag undergoes aging and stabilization treatment to fully dissolve free calcium oxide, and is screened and graded into three specifications: 19-26.5mm, 9.5-19mm, and 4.75-9.5mm. The stone powder and fine aggregate pass the incoming inspection, with a mud content of ≤3% and a moisture content fluctuation controlled within ±0.5%. Mineral powder, carbide slag, and desulfurized gypsum are premixed evenly according to the formula to form a composite cementitious material, which is then stored in a sealed, moisture-proof container.

[0033] S2. First, add all the coarse and fine aggregates and dry mix for 30 seconds. Then, add the composite cementitious material and continue to dry mix for 30 seconds. Add water at a moisture content of 4.69% and wet mix for 90 seconds. The discharge temperature is 52℃.

[0034] S3. Use sealed tank trucks for transportation, and control the transportation time within 1 hour; use pavers for continuous paving at a speed of 2.5 m / min, control the loose paving thickness according to a compaction coefficient of 1.28, and promptly address potholes, segregation, and road surface wave defects during the paving process.

[0035] S4. Initial compaction is carried out by two passes of static compaction with a steel wheel roller at a speed of 2.5 km / h; secondary compaction is carried out by four passes of high-frequency low-amplitude compaction with a vibratory roller at a speed of 3.5 km / h, with a compaction degree of 98.5% as measured on site; final compaction is carried out by two passes of static compaction with a rubber-tired roller at a speed of 2.5 km / h to eliminate wheel tracks and ensure a flat and dense base surface.

[0036] S5. Immediately after compaction, cover with geotextile and spray with water for 7 days to maintain moisture. Keep the base surface moist throughout the curing period. During the curing period, the entire road section will be closed to traffic, and no vehicles are allowed to pass. After curing, core samples were taken for testing. The unconfined compressive strength of the base layer after 7 days was 4.1 MPa; the road base surface was smooth and free of shrinkage cracks.

[0037] Example 2 This embodiment selects a road base construction project in a certain industrial park for on-site construction. The base design thickness is 18cm. The mix proportion of the road base construction mixture is as follows: coarse aggregate is graded steel slag, accounting for 65% of the total aggregate mass; fine aggregate is stone powder, accounting for 35% of the total aggregate mass. Among them, 19-26.5mm steel slag accounts for 17.3% of the total aggregate mass, 9.5-19mm steel slag accounts for 24.3% of the total aggregate mass, and 4.75-9.5mm steel slag accounts for 23.4% of the total aggregate mass; 2.35-4.75mm stone powder accounts for 6.4% of the total aggregate mass, and 0-2.35mm stone powder accounts for 28.6% of the total aggregate mass. Composite cementitious material is added externally at a dosage of 3.5% of the total aggregate mass, with the mass ratio of mineral powder, carbide slag, and desulfurized gypsum being 25:6:1. The moisture content of the mixture is controlled at 3.8%, and the measured maximum dry density is 2.51g / cm³. 3 .

[0038] The specific implementation process is as follows: S1. Steel slag undergoes aging and stabilization treatment to fully dissolve free calcium oxide, and is screened and graded into three specifications: 19-26.5mm, 9.5-19mm, and 4.75-9.5mm. The stone powder and fine aggregate pass the incoming inspection, with a mud content of ≤3% and a moisture content fluctuation controlled within ±0.5%. Mineral powder, carbide slag, and desulfurized gypsum are premixed evenly according to the formula to form a composite cementitious material, which is then stored in a sealed, moisture-proof container.

[0039] S2. First, add all the coarse and fine aggregates and dry mix for 30 seconds. Then, add the composite cementitious material and continue to dry mix for 30 seconds. Add water at a moisture content of 3.8% and wet mix for 90 seconds. The discharge temperature is 55℃.

[0040] S3. Use sealed tank trucks for transportation, and control the transportation time within 1 hour; use pavers for continuous paving at a paving speed of 3m / min, control the loose paving thickness according to a compaction coefficient of 1.25, and promptly address potholes, segregation, and road surface wave defects during the paving process.

[0041] S4. Initial compaction is carried out by static compaction once with a steel wheel roller at a speed of 2 km / h; secondary compaction is carried out by high-frequency low-amplitude compaction three times with a vibratory roller at a speed of 3 km / h, and the compaction degree is 98.2% as tested on site; final compaction is carried out by static compaction once with a rubber-tired roller at a speed of 2 km / h to eliminate wheel tracks and ensure that the base surface is flat and dense.

[0042] S5. Immediately after compaction, cover with geotextile and spray with water for 7 days to maintain moisture. Keep the base surface moist throughout the curing period. During the curing period, the entire road section will be closed to traffic, and no vehicles are allowed to pass. After curing, core samples were taken for testing. The unconfined compressive strength of the base layer after 7 days was 4.1 MPa; the road base surface was smooth and free of shrinkage cracks.

[0043] Example 3 This embodiment selects a township road base construction project for on-site construction. The base design thickness is 22cm. The mix proportion of the road base construction mixture is as follows: coarse aggregate is graded steel slag, accounting for 75% of the total aggregate mass; fine aggregate is stone powder, accounting for 25% of the total aggregate mass. Among them, 19-26.5mm steel slag accounts for 18.7% of the total aggregate mass, 9.5-19mm steel slag accounts for 29.9% of the total aggregate mass, and 4.75-9.5mm steel slag accounts for 26.4% of the total aggregate mass; 2.35-4.75mm stone powder accounts for 3.8% of the total aggregate mass, and 0-2.35mm stone powder accounts for 21.2% of the total aggregate mass. Composite cementitious material is added externally at a dosage of 4.5% of the total aggregate mass, with the mass ratio of mineral powder, carbide slag, and desulfurized gypsum being 26:7:1. The moisture content of the mixture is controlled at 6%, and the measured maximum dry density is 2.48g / cm³. 3 .

[0044] The specific implementation process is as follows: S1. Steel slag undergoes aging and stabilization treatment to fully dissolve free calcium oxide, and is screened and graded into three specifications: 19-26.5mm, 9.5-19mm, and 4.75-9.5mm. The stone powder and fine aggregate pass the incoming inspection, with a mud content of ≤3% and a moisture content fluctuation controlled within ±0.5%. Mineral powder, carbide slag, and desulfurized gypsum are premixed evenly according to the formula to form a composite cementitious material, which is then stored in a sealed, moisture-proof container.

[0045] S2. First, add all the coarse and fine aggregates and dry mix for 30 seconds. Then, add the composite cementitious material and continue to dry mix for 30 seconds. Add water at a moisture content of 6% and wet mix for 90 seconds. The discharge temperature is 48℃.

[0046] S3. Use sealed tank trucks for transportation, and control the transportation time within 1 hour; use pavers for continuous paving at a paving speed of 2m / min, control the loose paving thickness according to a compaction coefficient of 1.30, and promptly address potholes, segregation, and road surface wave defects during the paving process.

[0047] S4. Initial compaction is carried out by two passes of static compaction with a steel wheel roller at a speed of 3 km / h; secondary compaction is carried out by four passes of high-frequency low-amplitude compaction with a speed of 4 km / h, and the compaction degree is 98.6% as tested on site; final compaction is carried out by two passes of static compaction with a rubber-tired roller at a speed of 3 km / h to eliminate wheel tracks and ensure that the base surface is flat and dense.

[0048] S5. Immediately after compaction, cover with geotextile and spray with water for 7 days to maintain moisture. Keep the base surface moist throughout the curing period. During the curing period, the entire road section will be closed to traffic, and no vehicles are allowed to pass. After curing, core samples were taken for testing. The unconfined compressive strength of the base layer after 7 days was 4.3 MPa; the road base surface was smooth and free of shrinkage cracks.

[0049] Comparative Example 1 This comparative example uses the same raw materials and construction steps as Example 1, except that the composite cementitious material in Example 1 is replaced with an equal mass of ordinary Portland cement.

[0050] This comparative study uses a municipal road base construction project as an example. The base layer is designed to be 20cm thick. The mix proportions for the road base construction are as follows: coarse aggregate is graded steel slag, accounting for 70% of the total aggregate mass; fine aggregate is stone powder, accounting for 30% of the total aggregate mass. Specifically, 19–26.5mm steel slag accounts for 18% of the total aggregate mass, 9.5–19mm steel slag accounts for 27%, and 4.75–9.5mm steel slag accounts for 25%; 2.35–4.75mm stone powder accounts for 5%, and 0–2.35mm stone powder accounts for 25%. Ordinary Portland cement is added externally at a dosage of 4% of the total aggregate mass. The moisture content of the mixture is controlled at 4.69%, and the measured maximum dry density is 2.56 g / cm³. 3 .

[0051] The specific implementation process is as follows: S1. Steel slag undergoes aging and stabilization treatment to fully dissolve free calcium oxide, and is screened and graded into three specifications: 19-26.5mm, 9.5-19mm, and 4.75-9.5mm. The stone powder fine aggregate passes the incoming inspection, with a mud content of ≤3% and a moisture content fluctuation controlled within ±0.5%.

[0052] S2. First, add all the coarse and fine aggregates and dry mix for 30 seconds. Then, add ordinary Portland cement and continue to dry mix for 30 seconds. Add water at a moisture content of 4.69% and wet mix for 90 seconds. The discharge temperature is 52℃.

[0053] S3. Use sealed tank trucks for transportation, and control the transportation time within 1 hour; use pavers for continuous paving at a speed of 2.5 m / min, control the loose paving thickness according to a compaction coefficient of 1.28, and promptly address potholes, segregation, and road surface wave defects during the paving process.

[0054] S4. Initial compaction is carried out by two passes of static compaction with a steel wheel roller at a speed of 2.5 km / h; secondary compaction is carried out by four passes of high-frequency low-amplitude compaction with a vibratory roller at a speed of 3.5 km / h, and the compaction degree was tested at 98.3% on site; final compaction is carried out by two passes of static compaction with a rubber-tired roller at a speed of 2.5 km / h to eliminate wheel tracks and ensure that the base surface is flat and dense.

[0055] S5. Immediately after compaction, cover with geotextile and spray with water for 7 days to maintain moisture. Keep the base surface moist throughout the curing period. During the curing period, the entire road section is closed to traffic, and no vehicles are allowed to pass. After curing, core samples were taken for testing. The unconfined compressive strength of the base layer after 7 days was 4.2 MPa. However, multiple drying shrinkage cracks appeared on the surface of the road base layer during the curing period.

[0056] Comparative Example 2 This comparative example uses the same raw materials and construction steps as Example 1, the difference being that the gradation of the steel slag coarse aggregate is adjusted to two specifications, and no medium-sized steel slag with a size of 4.75 to 9.5 mm is added.

[0057] This comparative study uses a municipal road base construction project as an example. The base layer is designed to be 20cm thick. The mix proportions for the road base construction are as follows: coarse aggregate is graded steel slag, accounting for 70% of the total aggregate mass; fine aggregate is stone powder, accounting for 30% of the total aggregate mass. Specifically, 19–26.5mm steel slag accounts for 30% of the total aggregate mass, and 9.5–19mm steel slag accounts for 40%; 2.35–4.75mm stone powder accounts for 5%; and 0–2.35mm stone powder accounts for 25%. Composite cementitious materials are added externally at 4% of the total aggregate mass, with the mass ratio of mineral powder, carbide slag, and desulfurized gypsum being 77:20:3. The moisture content of the mixture is controlled at 4.69%, and the measured maximum dry density is 2.45g / cm³. 3 .

[0058] The specific implementation process is as follows: S1. Steel slag undergoes aging and stabilization treatment to fully dissolve free calcium oxide, and is screened and graded into two specifications: 19-26.5mm and 9.5-19mm. Stone powder and fine aggregate pass on-site inspection, with mud content ≤3% and moisture content fluctuation controlled within ±0.5%. Mineral powder, carbide slag, and desulfurized gypsum are premixed evenly according to the formula to form a composite cementitious material, which is then stored in a sealed, moisture-proof container.

[0059] S2. First, add all the coarse and fine aggregates and dry mix for 30 seconds. Then, add the composite cementitious material and continue to dry mix for 30 seconds. Add water at a moisture content of 4.69% and wet mix for 90 seconds. The discharge temperature is 52℃.

[0060] S3. Use sealed tank trucks for transportation, and control the transportation time within 1 hour; use pavers for continuous paving at a speed of 2.5 m / min, control the loose paving thickness according to a compaction coefficient of 1.28, and promptly address potholes, segregation, and road surface wave defects during the paving process.

[0061] S4. Initial compaction is carried out by two passes of static compaction with a steel wheel roller at a speed of 2.5 km / h; secondary compaction is carried out by four passes of high-frequency low-amplitude compaction with a vibratory roller at a speed of 3.5 km / h, and the compaction degree was tested at 97.1% on site; final compaction is carried out by two passes of static compaction with a rubber-tired roller at a speed of 2.5 km / h to eliminate wheel tracks and ensure that the base surface is flat and dense.

[0062] S5. Immediately after compaction, cover with geotextile and spray with water for 7 days to maintain moisture. Keep the base surface moist throughout the curing period. During the curing period, the entire road section will be closed to traffic, and no vehicles are allowed to pass. After curing, core samples were taken for testing. The unconfined compressive strength of the base layer after 7 days was 3.5 MPa; the road base surface was smooth and free of shrinkage cracks.

[0063] Table 1 compares the performance indicators of Examples 1-3 with those of Comparative Examples 1-2.

[0064] Table 1 Performance Indicator Comparison Table

[0065] A comprehensive comparison of the performance of Examples 1-3 and Comparative Examples 1-2 shows that the technical solution of the present invention exhibits significant advantages in multiple key performance dimensions. Regarding mechanical properties, all examples consistently meet the design strength requirements under different mix proportions, and no shrinkage cracks appear, indicating that the technical solution of the present invention has excellent crack resistance and a wide range of mix proportion adaptability. In contrast, although the strength of Comparative Example 1 slightly improved after replacing the composite cementitious material with pure cement, the high heat of hydration led to a large number of drying shrinkage cracks, severely affecting the durability of the base layer. In Comparative Example 2, the removal of 4.75–9.5 mm fine-grained steel slag resulted in a gap in aggregate gradation, a significant decrease in the density of the mixture, and the inability to meet the strength requirements. The above comparisons fully demonstrate that the present invention, through the synergistic combination of "continuously graded steel slag aggregate + ternary composite cementitious system," ensures both strength and density while also considering crack resistance, achieving an organic unity between solid waste resource utilization and improved base layer structural performance.

[0066] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.

Claims

1. A method for constructing a road base course using a multi-component waste residue compound as a substitute for water-stabilized crushed stone aggregate, characterized in that, The mixture used for road base construction consists of aggregates, composite cementitious materials, and water. The aggregates include coarse aggregates and fine aggregates, with the coarse aggregates accounting for 65% to 75% of the total aggregate mass. The composite cementitious material is added at 3.5% to 4.5% of the total aggregate mass. After wet mixing with water, the mixture has a moisture content of 3.8% to 6% and a dry density ≤ 2.58 g / cm³. 3 The construction method includes the following steps: S1. Weigh out the coarse aggregate, fine aggregate, and composite cementitious material according to the proportion of the mixture. S2. Dry mix the coarse aggregate and fine aggregate evenly, then add the composite cementitious material and dry mix evenly. Add water according to the moisture content of the mixture and wet mix. After mixing evenly, discharge the material. S3. The paving is carried out by sealed tank trucks to the construction site and continuously paved by a paver. The paving speed is controlled at 2 to 3 m / min, and the loose paving thickness is controlled according to the compaction coefficient of 1.25 to 1.

30. S4. Compact the molding process, with a compaction degree ≥98%; S5. After compaction, cover with geotextile and water for curing for no less than 7 days. During the curing period, traffic shall be closed.

2. The road base construction method for replacing water-stabilized crushed stone aggregate with multi-component waste residue compound according to claim 1, characterized in that, The coarse aggregate is graded steel slag, which consists of three particle sizes: 19–26.5 mm, 9.5–19 mm, and 4.75–9.5 mm, with a mass ratio of 1:1.4–1.6:1.35–1.

41.

3. The road base construction method for replacing water-stabilized crushed stone aggregate with multi-component waste residue compound according to claim 1, characterized in that, The fine aggregate is stone powder, which consists of two specifications: a particle size of 2.35–4.75 mm and a particle size of 0–2.35 mm, with a mass ratio of 1:4.5–5.

5.

4. The road base construction method for replacing water-stabilized crushed stone aggregate with multi-component waste residue compound according to claim 1, characterized in that, The composite cementitious material is composed of mineral powder, carbide slag, and desulfurized gypsum, with a mass ratio of 25-26:6-7:

1.

5. The road base construction method for replacing water-stabilized crushed stone aggregate with multi-component waste residue compound according to claim 1, characterized in that, In step S1, the coarse aggregate undergoes an aging and stabilization treatment to dissolve free calcium oxide.

6. The road base construction method for replacing water-stabilized crushed stone aggregate with multi-component waste residue compound according to claim 1, characterized in that, In step S2, the discharge temperature is ≤60℃.

7. The road base construction method for replacing water-stabilized crushed stone aggregate with multi-component waste residue compound according to claim 1, characterized in that, In step S3, the transportation time of the sealed tanker truck is ≤1 hour.

8. The road base construction method for replacing water-stabilized crushed stone aggregate with multi-component waste residue compound according to claim 1, characterized in that, In step S4, the compaction molding process specifically includes: Initial compaction: Static compaction with a steel wheel roller 1-2 times, travel speed 2-3 km / h; Compaction: Vibratory roller high-frequency low-amplitude compaction 3-4 times, travel speed 3-4 km / h; Final compaction: Apply static compaction with a rubber-tired roller 1-2 times at a speed of 2-3 km / h to eliminate wheel tracks and ensure a smooth and dense base surface.

9. The road base construction method for replacing water-stabilized crushed stone aggregate with multi-component waste residue compound according to claim 1, characterized in that, The 7-day unconfined compressive strength of the formed road base layer is not less than 4.1 MPa.

10. The road base construction method for replacing water-stabilized crushed stone aggregate with multi-component waste residue compound according to claim 1, characterized in that, This method is applicable to the base construction of municipal roads, highways, industrial park roads, factory roads, and rural roads.